2018
DOI: 10.1094/pdis-05-17-0758-re
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pathogens Associated with Psyllids and Leafhoppers in Capsicum annuum L. in the Mexican States of Durango, Zacatecas, and Michoacán

Abstract: In fall 2014, 5 to 75% percent of chili and bell pepper (Capsicum annuum L.) in commercial fields located in the Mexican states of Durango, Zacatecas, and Michoacán had symptoms of deformed, small, mosaic, curled, and chlorotic leaves; shortened internodes; plant dwarfing; or phyllody and rosetting leaf tips. At the same time, leafhoppers and psyllids were observed in the fields, and more than 50 beet leafhoppers (Circulifer tenellus) and nearly 300 potato psyllids (Bactericera cockerelli) were collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…In this study, the phytoplasma determined species, the number of tested insects and the determined phytoplasmas in pepper fields are given in Table 2. (Swisher et al, 2018), Iran MK379605 (Babaei et al 2020) and MG788318 (unpublished data), 99.60% similarity rate to Iran isolate JF508509 (Jamshidi et al 2014). The isolate MT992796 identified as Ca.…”
Section: Phytoplasma Detectionmentioning
confidence: 90%
“…In this study, the phytoplasma determined species, the number of tested insects and the determined phytoplasmas in pepper fields are given in Table 2. (Swisher et al, 2018), Iran MK379605 (Babaei et al 2020) and MG788318 (unpublished data), 99.60% similarity rate to Iran isolate JF508509 (Jamshidi et al 2014). The isolate MT992796 identified as Ca.…”
Section: Phytoplasma Detectionmentioning
confidence: 90%
“…Mixed infections confirmed that the two phytoplasmas were actively acquired and mixed infection rates of about 24% were recorded. Mixed infections of phytoplasmas in vector insects are quite common (Bosco and D'Amelio, 2010), and, among psyllids, Bactericera cockerelli can host more than one phytoplasma species (16SrI-A and VI-A), together with the unrelated 'Candidatus Liberibacter solanacearum', with frequencies of up to 40% (Swisher et al, 2018). (Queiroz et al, 2016) are challenging this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed infections by bacterial pathogens are commonly observed in the phloem of a single plant. The simultaneous occurrence of multiple pathogens, either related or phylogenetically distant, is rather frequent in single herbaceous plants and trees of many families (Križanac et al., ; Nicolaisen et al., ; Arratia‐Castro et al., ; Satta et al., ; Swisher et al., ). Throughout its life cycle, a single insect may feed on several plants of the same or different species, probably being exposed to mixed pathogen infections.…”
Section: Multiple Pathogen Infections and Competitionmentioning
confidence: 99%
“…Throughout its life cycle, a single insect may feed on several plants of the same or different species, probably being exposed to mixed pathogen infections. As a consequence, insect vectors may acquire many pathogen species or strains during a feeding event, or by feeding sequentially on host plants infected by different bacteria (Križanac et al., ; Raddadi et al., ; Swisher et al., ) (Table ). In some cases, the co‐occurrence of multiple pathogens in an insect's body is inhibited by interferential interactions such as selective acquisition or transmission of a single microbe (Bosco & D'Amelio, ).…”
Section: Multiple Pathogen Infections and Competitionmentioning
confidence: 99%